Research on Advanced Control Method of Multiple Photovoltaic Strings Input Type Recognition - Wang, Yiwang; Zhang, Bo; Zhang, Yao; Chen, Xiaogao (Frontiers in Energy Research, 2022)
In order to decrease the performance effect of a single string in part of a photovoltaic (PV) array and increase the adaptive PV power generation, independent multiple series-connected PV strings are usually adopted in PV system projects to implement the input configuration. Besides, the conversion circuits with multipath inputs are required to be designed for the corresponding inverters to carry out the control algorithms. Since independent and parallel-connected modes exist for the PV strings input in actual engineering projects, it is of great significance to effectively identify different PV inputs automatically for inverter inputs. In order to solve the problems of high hardware circuit requirements and complicated control algorithms in most of the existing control methods, a multiple PV strings input type recognition method is proposed. The proposed method is free from increasing the inverter hardware cost, and it enhances the capability of identification and judgement. Moreover, experiments and engineering applications are implemented to verify the proposed control method.